2011
DOI: 10.1111/j.1471-0528.2011.03065.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smoking cessation counselling in pregnant women: a meta‐analysis of randomised controlled trials

Abstract: Background Pregnant smokers are often prescribed counselling as part of multicomponent cessation interventions. However, the isolated effect of counselling in this population remains unclear, and individual randomised controlled trials (RCTs) are inconclusive.Objective To conduct a meta-analysis of RCTs examining counselling in pregnant smokers.Search strategy We searched the CDC Tobacco Information and Prevention, Cochrane Library, EMBASE, Medline and PsycINFO databases for RCTs evaluating smoking cessation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 40 publications
1
37
0
2
Order By: Relevance
“…Smoking during pregnancy is the largest preventable cause of low birth weight, prematurity, intrauterine growth restriction, and perinatal mortality (20,21); sadly, more than 50% of smokers who become pregnant continue to smoke (7,8). The incidence of smoking during pregnancy varies widely across the United States, with at least 12% of pregnant women continuing to smoke (22).…”
Section: Effects Of Maternal Smoking During Pregnancy On Lung Developmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking during pregnancy is the largest preventable cause of low birth weight, prematurity, intrauterine growth restriction, and perinatal mortality (20,21); sadly, more than 50% of smokers who become pregnant continue to smoke (7,8). The incidence of smoking during pregnancy varies widely across the United States, with at least 12% of pregnant women continuing to smoke (22).…”
Section: Effects Of Maternal Smoking During Pregnancy On Lung Developmentioning
confidence: 99%
“…Although nicotine replacement therapy has been used during pregnancy (5,6), on the basis that nicotine alone will be safer than conventional cigarette use, the potential continued use of e-cigarettes by e-cigarette-only users during pregnancy raises heightened safety concerns of e-cigarette use during pregnancy. The fact that about half of conventional cigarette users continue to smoke while pregnant (7,8) suggests that significant numbers of e-cigarette users will also continue e-cigarette use during pregnancy, thus exposing the fetus to nicotine. As described later, the developing lung is particularly sensitive to the effects of nicotine, suggesting that e-cigarette use during pregnancy may affect lung development.…”
mentioning
confidence: 99%
“…One review, for instance, examined eights studies for the effect of isolated smoking cessation counseling programs in pregnant women and concluded that the intervention (i.e.,counseling) was not statistically better than the controls in increasing abstinences following the program, despite an overall 4% difference in cessation rates favoring the intervention groups (50). The time for each counseling session varied from 180 minutes to 600 minutes and this could be a possible reason why there was no significant difference found.…”
Section: Behavior Therapymentioning
confidence: 60%
“…Currently there is not enough evidence to suggest that CBT on its own would be an effective intervention to recommend (50). NRT compared to cigarettes has shown an increase in birth weight (40) and a decrease in maternal blood pressure (41) and therefore it has been suggested that it would be better to recommend NRT during pregnancy to reduce the number of cigarettes smoked and increase the possibility of quitting.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of evidence-based guidelines, there is variable uptake by nurses, midwives, and physicians in implementing practice recommendations [17][18][19][20]. Specifically, these studies have identified conflicting advice, inconsistent application of smoking cessation interventions, and lack of follow-up, as common problems.…”
Section: Introductionmentioning
confidence: 99%